Komunikasi Interpersonal Barista Coffee Shop - Alya Nurulaeni; Aning Sofyan (UNISBA Press, 2023)
Abstract. Currently, the coffee shop business is one of the businesses that is mushrooming throughout Indonesia, because coffee shops are considered a gathering place that is in great demand today by all types of people. NAMA Coffee is one of the MSME-based coffee shops in Cimahi City that has survived from 2018 to the present. In the development of this increasingly diverse coffee shop business, of course, NAMA Coffee must have uniqueness and distinctiveness so that it is remembered and remembered by consumers, one way is to improve, or add to the quality of service to consumers by conducting interpersonal communication interactions carried out by NAMA Coffee baristas to consumers. The research used a qualitative method with a case study approach, interpersonal communication theory. The results of this study are the interpersonal communication of NAMA Coffee baristas to consumers by describing the interpersonal communication process of NAMA Coffee baristas to consumers, barriers to interpersonal communication of NAMA Coffee baristas to consumers when interacting, and the purpose of NAMA Coffee baristas implementing interpersonal communication to consumers in running a business in a coffee shop. Interpersonal communication interactions carried out by baristas can change the concept of